Beauty hegemony in the online beauty community a phenomenological study on Filipino influencers on TikTok - Espinosa, Ryanna Dominique D.; Bautista, Roehl Niño (Quezon City University of the Philippines Diliman, 2025)
This study examined whether select Filipino TikTok beauty influencers reinforce or challenge hegemonic beauty ideologies. The rise of influencer marketing revealed that beauty influencing is an inherently commercial role. While so, they also act as tastemakers and cultural gatekeepers within the online Filipino beauty community, capable of shaping minds and influencing viewers to adhere to dominant beauty ideologies. This strengthens that beauty influencers can resist or reinforce beauty hegemony as they navigate their lived experiences as content creators. Using Gramsci’s theory of cultural hegemony, this study answered its research problem by (1) describing the lived experiences of select Filipino TikTok beauty influencers, (2) identifying emerging themes and patterns, and (3) analyzing how beauty influencers’ lived experiences reflected a war of position towards current dominant beauty ideologies. In-depth interviews with five Filipino TikTok beauty influencers, selected through purposive sampling, were transcribed and used for thematic analysis. Meaning units were identified, synthesized into emergent themes, and analyzed to uncover the influencers’ positionality towards beauty hegemony.
Thesis
Keywords: Beauty, Personal -- Social aspects -- Philippines; Mass media -- Influence -- Philippines; Online social networks -- Social aspects -- Philippines